Neglected Achilles tendon ruptures: literature review - Prioli Leite, Raul; Ayusso Correa Sossa, Felipe; Santos Prata, Sergio Damiao; Osório Neto, Ernane Bruno; Rolim Queiroz, Marcel; da Rocha Macedo, Rafael (Journal of the Foot & Ankle, 2026)
Introduction: Achilles tendon rupture is the most common lower limb tendon injury, with rising incidence in active adults. Up to 25% are initially neglected, becoming chronic after four weeks and leading to functional impairment. This study reviews current treatments, outcomes, and complications of neglected Achilles tendon ruptures. The objective is to review the literature on current treatments for neglected Achilles tendon ruptures, their outcomes, and potential complications. Methods: A bibliographic review of the state of the art was conducted in national and international databases. Articles published in indexed journals between 1991 and 2022 that addressed the treatment of Achilles tendon ruptures with more than four weeks of evolution were selected; however, only articles with less than 22 years of publication (2000-2022) were analyzed. Results: Surgical treatment is well established for patients with significant functional demands. The various surgical techniques described in the literature and currently used have similar success rates and complication profiles, particularly regarding patient satisfaction, functional outcomes, anthropometric measurements, and return to work and sports activities. Conclusion: Several techniques can be used to treat neglected Achilles tendon ruptures. When choosing the most appropriate technique, gap size, patient characteristics, and surgeon experience should be considered.